Evidence-based public health effectiveness and efficiency - Killoran, Amanda; Kelly, Michael P. (Michael Patrick), 1953- (Oxford : Oxford University Press, 2010)
Public health decisions are often based on short-term demands rather than long-term study, and policies & programs are sometimes developed from anecdotal evidence. To enhance evidence-based practice, this book provides practical guidance on the methodology and evaluation of such programs & policies.
Description based on print version record.
Includes bibliographical references and index.
Keywords: National Institute for Health and Clinical Excellence (Great Britain); Public health -- Research -- Methodology; Evidence-based medicine; Public health administration -- Great Britain -- Evaluation; Evidence-based medicine -- Great Britain -- Evaluation